The effect of different radiation sources for the UV curing of a screen‐printed, water‐based polyurethane acrylate binder. (3rd May 2016) - Akbulut, Gökhan; Karagüzel Kayaoğlu, Burçak; Eren, Mesut; Yıldız, Bülent; Orbay, Murat
Abstract : In this paper, titanium‐dioxide‐pigmented printing pastes of water‐borne, UV‐curable polyurethane acrylate binder with two different UV‐curing photoinitiator combinations were prepared and screen printed on a black t‐shirt fabric. The effects of mercury and gallium radiation sources employed either singly or in combination for UV curing and the total energy level on the printing performance were investigated. The cured textile samples were subjected to colour measurements before and after five cycles of washing, and hiding power and changes in chromacity, hue, and colour were determined. Single‐lamp applications of mercury and gallium were not satisfactory, and opaque pigment hindered deep curing, especially at thicker coating levels. It was found that employment of a mercury–gallium lamp system applying an irradiation at medium level can provide pigment printing of opaque white inks with excellent coverage, washing resistance, and medium hardness.